Simulink model of Mel Frequency Cepstral Coefficient analysis for extracting asphyxiated infant cry features - Mohebbi Zulfikar, Mohd Ali; Wahida, Mansor; Lee, Yoot Kuan, Dr.; Azlee, Zabidi (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/